2019
DOI: 10.1177/2325967119867618
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocytes From Device-Minced Articular Cartilage Show Potent Outgrowth Into Fibrin and Collagen Hydrogels

Abstract: Background: Transplantation of autologous minced cartilage is an established procedure to repair chondral lesions. It relies on the migration of chondrocytes out of cartilage particles into a biomaterial. So far, there is no efficient way to finely mince cartilage. No consensus exists on the nature of the biomaterial to be used to promote chondrocyte migration. Purpose/Hypothesis: This study aimed to investigate the potential clinical use of a custom-made mincing device as well as a possible alternative biomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 36 publications
2
53
0
Order By: Relevance
“…A growing body of evidence has shown that chondrocyte migration can be improved and accelerated by creating an appropriate matrix microenvironment. Levinson et al (2019) embedded cartilage particles into fibrin and collagen gels, and observed significant chondrocyte outgrowth after 28 days in culture. Ng et al (2012) reported that a macro-porous polyvinyl alcohol (PVA) scaffold facilitated chondrocyte migration from host cartilage into scaffold and improved interface integration in an in vitro cartilage defect model.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has shown that chondrocyte migration can be improved and accelerated by creating an appropriate matrix microenvironment. Levinson et al (2019) embedded cartilage particles into fibrin and collagen gels, and observed significant chondrocyte outgrowth after 28 days in culture. Ng et al (2012) reported that a macro-porous polyvinyl alcohol (PVA) scaffold facilitated chondrocyte migration from host cartilage into scaffold and improved interface integration in an in vitro cartilage defect model.…”
Section: Discussionmentioning
confidence: 99%
“…With increased surface area, bioactive factors present in minced cartilage grafts are better able to interact with marrow elements, such as mesenchymal stem cells, recruited to the lesion without the need to grow chondrocytes ex vivo. 26 , 27 , 28 , 29 Tissue grafts prepared with Reveille CP (Exactech Inc.) are composed primarily of tissue particles between 0.3 mm and 1.0 mm in diameter, representing a 10-fold increase in surface area over that of intact articular cartilage, with exposure of cells on the surface of the particles. Fluorescent microscopy analysis has demonstrated high cellular viability in graft fragments following processing with Reveille CP.…”
Section: Discussionmentioning
confidence: 99%
“…By that cartilage is harvested, minced into small fragments (paste-like), and collected at once. 16 , 17 Subsequently, the minced cartilage is mixed with 2 to 3 drops of PRP, resulting in a malleable substance ( Fig 2 D).…”
Section: Surgical Techniquementioning
confidence: 99%